2023
DOI: 10.1038/s41593-023-01283-x
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal spatio-predictive cognitive maps adaptively guide reward generalization

Abstract: The brain forms cognitive maps of relational knowledge—an organizing principle thought to underlie our ability to generalize and make inferences. However, how can a relevant map be selected in situations where a stimulus is embedded in multiple relational structures? Here, we find that both spatial and predictive cognitive maps influence generalization in a choice task, where spatial location determines reward magnitude. Mirroring behavior, the hippocampus not only builds a map of spatial relationships but als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 84 publications
3
16
0
Order By: Relevance
“…When different stimulus dimensions become relevant at different times, the parallel coding of multiple knowledge structures allows for flexible selection of relevant information. Such cognitive computations enable the hippocampus to adaptively generalize based on task demands ( Garvert et al. 2023 ) and to guide goal-directed behavior in novel situations ( Whittington et al.…”
Section: Discussionmentioning
confidence: 99%
“…When different stimulus dimensions become relevant at different times, the parallel coding of multiple knowledge structures allows for flexible selection of relevant information. Such cognitive computations enable the hippocampus to adaptively generalize based on task demands ( Garvert et al. 2023 ) and to guide goal-directed behavior in novel situations ( Whittington et al.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies showed relatively quick learning of regularities [130][131][132] and generalization based on such regularities 120 in a single lab session. The hippocampus, known to be involved in rapid learning 67,128,133,134 and in event segmentation 113,[135][136][137] , also mediates learning the structure of the environment 131,[138][139][140][141][142][143][144][145][146][147][148][149] . Thus, converging behavioral and neural evidence suggest that rapid initial learning largely shapes our schemas.…”
Section: Box 1: Rapid Learning In the Hippocampus Shapes New Schemasmentioning
confidence: 99%
“…Though a full understanding of this effect would require future work aimed at studying the relationship in detail, we speculate that reward drives stronger contextual encoding as a means of incorporating any potentially informative features into the representation. Indeed, prior studies show that reward states drive contextual coding (Wolosin et al, 2013) and modulate map-like representations (Garvert et al, 2023).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%